Effect of boron carbide reinforcement on properties of stainless-steel metal matrix composite for nuclear applications - Van Dong Pham; Phan Nguyen Huu; Patil Santosh; Shirguppikar Shailesh; Kalel Sudarshan; Thanh Le Thi Phuong; Hien Do Minh (Journal of the Mechanical Behavior of Materials, 2022)
Stainless steel (SS304) is a widely used material in underwater nuclear applications due to its superior corrosion resistance and high strength. Along with these superior properties, the application demands neutron absorption and high wear resistance under dynamic operations. The ceramic reinforcements help to enhance these properties of metal alloy with a suitable composite design. The present work deals with the development of high wear-resistant and radiation (nuclear) tolerant boron carbide (B4C)–SS 304 composite material. SS304 metal matrix with 0–5 vol% of B4C ceramic reinforcement is produced by powder metallurgy technique. The presence of reinforcement was confirmed with X-ray diffraction analysis. Properties such as density, hardness, and water absorption are measured. A pin-on-disc tribology study is conducted to evaluate the coefficient of friction and wear of developed compositions at a sliding distance of 200 m, contact load of 10 N, and sliding speed of 1 and 5 m/s under dry lubrication conditions. The lowest density of 2.96 g/cc was noted for 15% B4C-reinforced composite as compared to the density of SS304 metal matrix (5.71 g/cc). The water absorption capacity of the composite was increased with percentage reinforcement, and it was found 62% higher than the unreinforced matrix. The hardness of composite increases with B4C particle reinforcement and maximum microhardness of 153 HV was measured for 15 vol% reinforced composites. Wear and coefficient of friction decrease with an increase in the percentage of B4C particles. At 15 vol% of B4C in the composite, lowest wear (1.91 mm3@1 m/s and 2.51 mm3@5 m/s) and COF (0.021@1 m/s and 0.042@5 m/s) were observed. This suggests that the developed composite can be effectively used in low-pressure–high-speed nuclear applications.